Implementation of the Think Pair Share Model on the Material of Light and its Properties on Students' Critical Thinking Skills - Purmiatin, Aprilita Ika; Prameswari, Noviardani Kartika (Academia Publication, 2025)
The purpose of this study is (1) to describe the implementation of the think-pair-share model on the material of light and its nature on students' critical thinking skills. (2) to determine students' critical thinking skills in the think-pair-share model on the material of light and its nature. Qualitative research techniques were used in this study, while a descriptive approach was used to present the results of the study. The Think Pair Share model directly involves students in the learning process through group activities, practicums, and problem-solving discussions so that the Think Pair Share model can foster students' critical thinking skills. Students can think critically about the material of light and its nature. In learning the Think Pair Share model, students can formulate questions and identify relevant information. Students are able to determine a problem-solving plan in practice. Students are able to determine the right solution to the problem. Students are also able to draw conclusions and review all answers.